The validity of ICD codes coupled with imaging procedure codes for identifying acute venous thromboembolism using administrative data - Alotaibi, Ghazi S; Wu, Cynthia; Senthilselvan, Ambikaipakan; McMurtry, M Sean (Vascular medicine (London, England), 2015)
The purpose of this study was to evaluate the accuracy of using a combination of International Classification of Diseases (ICD) diagnostic codes and imaging procedure codes for identifying deep vein thrombosis (DVT) and pulmonary embolism (PE) within administrative databases. Information from the Alberta Health (AH) inpatients and ambulatory care administrative databases in Alberta, Canada was obtained for subjects with a documented imaging study result performed at a large teaching hospital in Alberta to exclude venous thromboembolism (VTE) between 2000 and 2010. In 1361 randomly-selected patients, the proportion of patients correctly classified by AH administrative data, using both ICD diagnostic codes and procedure codes, was determined for DVT and PE using diagnoses documented in patient charts as the gold standard. Of the 1361 patients, 712 had suspected PE and 649 had suspected DVT. The sensitivities for identifying patients with PE or DVT using administrative data were 74.83% (95% confidence interval [CI]: 67.01–81.62) and 75.24% (95% CI: 65.86–83.14), respectively. The specificities for PE or DVT were 91.86% (95% CI: 89.29–93.98) and 95.77% (95% CI: 93.72–97.30), respectively. In conclusion, when coupled with relevant imaging codes, VTE diagnostic codes obtained from administrative data provide a relatively sensitive and very specific method to ascertain acute VTE.